2014
DOI: 10.1093/aob/mcu073
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death in kiwifruit stigmatic arms and its relationship to the effective pollination period and the progamic phase

Abstract: The data provide evidence to support the hypothesis that PCD processes occurring in the secretory tissue of non-pollinated kiwifruit stigmatic arms could be the origin for the observed short effective pollination period. The results obtained in the secretory tissue of pollinated kiwifruit stigmatic arms upon pollination support the idea that PCD might be accelerated by pollination, pointing to the involvement of PCD during the progamic phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 42 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…The investigation of floral longevity and EPP is a challenging field of plant biology, and of importance in both the horticultural as well as the agricultural context. In fruit producing crops, a short EPP can represent a major restriction for yield stability 40,47 . Also in staple crops such as wheat, rice, or maize, optimization of the period of floral receptivity could contribute to stabilization of seed yield, particularly under adverse environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of floral longevity and EPP is a challenging field of plant biology, and of importance in both the horticultural as well as the agricultural context. In fruit producing crops, a short EPP can represent a major restriction for yield stability 40,47 . Also in staple crops such as wheat, rice, or maize, optimization of the period of floral receptivity could contribute to stabilization of seed yield, particularly under adverse environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the EPP in fruits varies and can be from one day, as found in pear cultivar 'Doyenné du Comice' [15] up to 12 days in peach cultivar 'Earlihale' [32] and some olive cultivars [33]. EPP has been studied in many temperate and subtropical fruit species, such as apple [30,34], pear [35], japanese quince [36], peach [37], apricot [38], sweet cherry [39], sour cherry [21], almond [40], olive [41], red currant [42], rabbiteye blueberry [43], kiwi [13,44], mango [45], avocado [46], and some citruses [47].…”
Section: Effective Pollination Periodmentioning
confidence: 99%
“…In flowers of Nicotiana tabacum, ethylene production increases rapidly following pollination (De Martinis et al 2002) and plays an important role in triggering the degeneration of cells comprising the transmission tract of the style, thus aiding the passage of pollen tubes through this tissue (Wang et al 1996). Ferradás et al (2014) have further shown that cellular changes indicative of programmed cell death are accelerated by pollination in stigmas and styles of kiwi fruit (Actinidia chinensis var. deliciosa).…”
Section: Further Considerations and Future Directionsmentioning
confidence: 99%